Legal Protection of Health Workers Who Experience Violence from Patients and Their Families in the Time of the Covid-19 Pandemic - Eddy Rifai; Nurul Purna Mahardika; Arini Weronica; Husna Purnama; Nila Sari Dewi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Along with the number of deaths among health workers during the COVID-19 pandemic, violence against health workers also often occurs. This shows that there is a need for an analysis related to legal protection for health workers. The problems that will be discussed in this research are: What are the legal provisions related to protection for health workers during the COVID-19 pandemic? And what about legal protection for health workers who experience violence The research method uses a normative juridical approach with qualitative analysis. The results of the study indicate that legal protection is an effort to maintain the rights of individuals or groups that can be fulfilled from strong or powerful parties such as the government or businessmen and other parties for the creation of security and public order. Legal protection for health workers is regulated in Article 57 of Law no. 36 of 2014 concerning Health Workers. Meanwhile, health workers who have been attacked have been protected and regulated in Articles 170 and 351 of the Criminal Code.